2021
DOI: 10.3390/molecules26216534
|View full text |Cite
|
Sign up to set email alerts
|

Design and Antioxidant Properties of Bifunctional 2H-Imidazole-Derived Phenolic Compounds—A New Family of Effective Inhibitors for Oxidative Stress-Associated Destructive Processes

Abstract: The synthesis of inhibitors for oxidative stress-associated destructive processes based on 2H-imidazole-derived phenolic compounds affording the bifunctional 2H-imidazole-derived phenolic compounds in good-to-excellent yields was reported. In particular, a series of bifunctional organic molecules of the 5-aryl-2H-imidazole family of various architectures bearing both electron-donating and electron-withdrawing substituents in the aryl fragment along with the different arrangements of the hydroxy groups in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…The results suggest that introduction of nitro substituent remarkably improved antioxidant activity when 14c and 14d were compared (Table 1). This result is in accordance with a previous study reporting enhanced antioxidant capacity for imidazole derivatives with nitro groups (Gerasimova et al, 2021) [35].…”
Section: Synthesis and Characterizationsupporting
confidence: 94%
“…The results suggest that introduction of nitro substituent remarkably improved antioxidant activity when 14c and 14d were compared (Table 1). This result is in accordance with a previous study reporting enhanced antioxidant capacity for imidazole derivatives with nitro groups (Gerasimova et al, 2021) [35].…”
Section: Synthesis and Characterizationsupporting
confidence: 94%
“…Previously, we have described and successfully applied a potentiometric approach have been study antioxidant properties using the Ox-Red components of the system on an example of the K 3 [Fe(CN) 6 ]/K 4 [Fe(CN) 6 ], for a wide range of objects [ 19 , 21 , 22 , 23 ]. However, the use of this approach for other models of oxidizing agents is difficult due to the inaccessibility of the Red component of the system, and consequently, the complexity of using two components of the system simultaneously.…”
Section: Resultsmentioning
confidence: 99%
“…For the successful implementation of this concept, the requirements for the models of oxidizing agent, used in the methods for studying AO properties, were formulated. Approaches to the potentiometric study of antioxidants, based on the reactions of electron and hydrogen atom transfer, have been successfully developed by our group for a long time [ 18 , 19 , 20 , 21 , 22 , 23 ]. Previously, we have shown that reactions with radical systems can be studied by the potentiometric method [ 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations